Research on the Control System of the Converter for Oil Drilling Drive - JIANG Ping; MEI Wenqing; YANG Dacheng; ZHOU Zhiyu; GAN Weiwei; CHEN Tao (Kongzhi Yu Xinxi Jishu)
Aiming to the load characteristic of oil drilling drive system, ARM+DSP+FPGA as the main control system of the control framework for oil inverter is proposed, and also the main circuit structure of converter, the principle of asynchronous motor vector control, the framework of indirect vector control-orientation and the master-slave control mode are analyzed and explained. The results of the oil field application show that the control system has a good dynamic response performance and control performance.